The Laser Cleaning Process for the Removal of Surface Corrosion Developed over One Year on Stainless Steel SS304 - R. Linggamm; M. M. Quazi; M. H. Aiman; J. Farzad; M. Nasir Bashir (Journal of ICT, Design, Engineering and Technological Science, 2020)
Stainless steel SS304 is one of the most widely employed steel alloys used in a wide variety of industries. However, under certain atmospheric and environmental conditions, it is likely to corrode. High humidity can cause damage to the native chromium oxide layer, causing rust formation. Once the corrosion develops, it becomes difficult to remove the rust layer locally and chemically treated or dry blasted. But recently, a novel application of laser surface irradiation can be employed to remove the corrosion products formed on the surface rapidly and robustly. The laser corrosion removal process is a non-mechanical technique that can remove rust from difficult-to-reach areas with high efficiency. However, the rust removal depends on the laser de-rusting process parameters. This work studies the effect of laser corrosion removal parameters such as power, frequency, and several loops with an optical microscope to observe surface features. Results indicate that the number of loops is a significant parameter that enhances corrosion removal significantly. Additionally, the selection of correct frequency, power and scanning speed, and hatching distance also play a significant role in corrosion removal efficiency. Using a low-power fiber laser marking machine to remove corrosion from metal samples will provide energy savings for the commercialization of such a process.